STRATEGI KEPALA SEKOLAH DALAM PENGELOLAAN SARANA DAN PRASARANA PENDIDIKAN - Wahidin Wahidin Wahidin (Manajer Pendididikan, 2015)
The purpose of this research was described the strategic of the principle in the management facility and infrastructure education at senior high school number 8 Lubuk Linggau city. The research used the descriptive qualitative method. The subject is principle, deputy Principle study facility and infrastructure, teacher, and students.The data collecting used interviev, observation, and documentation. The tecnigue analizing data are data reduction, data display andconclusion or verification. The result of this research was improving the principle’s management of facility and infrastructure the strategi as procurement Planning, procurement process, inventory,utilization, maintenance, and monitoring.Keyword: strategic, principle, management, facility.